Natural Human Immunity Against Staphylococcal Protein A Relies on Effector Functions Triggered by IgG3 - Boero, Elena; Cruz, Ana Rita; Pansegrau, Werner; Giovani, Cinzia; Rooijakkers, Suzan H. M.; van Kessel, Kok P. M.; van Strijp, Jos A. G.; Bagnoli, Fabio; Manetti, Andrea G. O. (Frontiers in Immunology, 2022)
Staphylococcal protein A (SpA) is a multifunctional, highly conserved virulence factor of Staphylococcus aureus. By binding the Fc portion of all human IgG subclasses apart from IgG3, SpA prevents correct antibody and complement deposition on the bacterial surface, impairing staphylococcal clearance by phagocytosis. Because of its anti-opsonic properties, SpA is not investigated as a surface antigen to mediate bacterial phagocytosis. Herein we investigate human sera for the presence of SpA-opsonizing antibodies. The screening revealed that sera containing IgG3 against SpA were able to correctly opsonize the target and drive Fcγ receptor-mediated interactions and phagocytosis. We demonstrated that IgG3 Fc is significantly more efficient in inducing phagocytosis of SpA-expressing S. aureus as compared to IgG1 Fc in an assay resembling physiological conditions. Furthermore, we show that the capacity of SpA antibodies to induce phagocytosis depends on the specific epitope recognized by the IgGs on SpA molecules. Overall, our results suggest that anti-SpA IgG3 antibodies could favor the anti-staphylococcal response in humans, paving the way towards the identification of a correlate of protection against staphylococcal infections